Dynamic heat transfer analysis of liquefied natural gas ambient air vaporizer under frost conditions. (5th January 2017) - Liu, Shanshan; Jiao, Wenling; Ren, Lemei; Wang, Haichao; Zhang, Ping
Highlights: A coupled dynamic heat transfer model for the AAV is established. The peak thermal resistance temperature should be avoided for the operation. Frost formation changes the coupled heat transfer coefficient of the AAV. The effective operation time gets shorter as the air temperature gets lower. Abstract: Liquefied natural gas (LNG) ambient air vaporizer (AAV) is a cryogenic heat exchanger, which utilizes ambient air to evaporate LNG in gas terminal stations. The moist air around the AAV fin tube may freeze during the long-time operation, leading to a worse heat transfer performance. Study on the dynamic heat transfer performance of AAV is required for its optimal design and operation. This paper presents a coupled dynamic heat transfer model, which incorporates the cryogenic frost formation and flow boiling heat transfer of LNG. The model was demonstrated in the heat transfer analysis of a typical star-fin type AAV. The model results were validated by the test data of a commercial HAI848F type AAV. The dynamic heat transfer performance of AAV under frost conditions was also studied.